Exploring the Effects of Ikigai on Mental, Physical, and Social Health: A Scoping Review - Ijeoma Ijeaku; Armaan Zare; Ola Egu; Ihuoma Chukwueke; Onyinye Onwuzulike (Lifestyle Medicine)
ABSTRACT There has been growing recognition of the importance of cultural factors in shaping health outcomes. There is an established interconnectedness among meaning, purpose, and health. Understanding cultural factors, which support a positive linear effect on health, could help establish their role in medical practice and lifestyle practices across various cultures. Ikigai is a Japanese term coined from two words—“iki” meaning “to live” and “gai” meaning “reason”—and became a concept in the early 20th century. Mieko Kamiya, a Japanese psychiatrist, pioneered Ikigai research in 1966, and most of the research studies supporting its usefulness have come from Japanese communities. In this first‐ever scoping review of the effects of Ikigai on various aspects of health, as defined by the World Health Organization, we report findings from 86 articles after an extensive review process involving a validated website‐based screening and data extraction tool. By examining the available evidence in a scoping review, we aim to provide a comprehensive overview of the current knowledge regarding Ikigai and its implications for clinical practice and future research. Although our primary focus is on mental health outcomes, we examined the potential impact on physical and social health measures. Findings indicate that Ikigai positively influences depression scores, helps cultivate a sense of purpose, and enhances well‐being and life satisfaction. Further, Ikigai is associated with a reduced risk of all‐cause mortality and functional disability, additionally increasing social connectedness and participation in recreation and employment. Through this effort, this review aims to bridge the gap between non‐traditional philosophies and traditional approaches to mental health treatment, fostering a more inclusive and culturally sensitive framework for promoting psychological well‐being and health in diverse populations.